Seeding young entrepreneurs: The role of business incubators - Ana Rosado-Cubero; Adolfo Hernández; Francisco José Blanco-Jiménez; Teresa Freire-Rubio (Journal of Innovation & Knowledge)
This study focusses on young entrepreneurs and considers the extent of business incubators’ impact on the development and visibility of projects headed by young people. To do so, we analyse incubators’ role as ecosystems for entrepreneurship in Spain based on the 2023 Funcas survey. First, we categorised incubators according to entrepreneurs’ age, defining young incubators as those in which most of the businesses are run by individuals under 35, excluding those over that age. We analyse variables that include the services offered and the frequency of events or training within the incubators to determine which approaches benefit or harm young entrepreneurs. This study uses a statistical approach, with quantitative data from the questionnaire as a starting point to characterise and identify young entrepreneurial profiles in business incubators. We develop and test two hypotheses using the chi-squared test, which is a non-parametric (distribution free) technique. Finally, we include a brief analysis of young entrepreneurs’ personality traits to shed light on some defining characteristics, concluding that personal initiative is a key feature amongst entrepreneurs under the age of 35. We conclude that the incubator system in Spain harms young entrepreneurs and propose some relevant recommendations to reverse this trend.